Effects of Mastalgia in Young Women on Quality of Life, Depression, and Anxiety Levels - Kanat, Burhan Hakan; Atmaca, Murad; Girgin, Mustafa; Ilhan, Yavuz Selim; Bozdag, Ahmet; Ozkan, Zeynep; Emir, Seyfi (Springer India, 2016)
The aims of this study are to evaluate whether or not there is a relationship between mastalgia with anxiety and depression in young women with mastalgia who do not have organic breast pathology and to examine the effect of pain on the quality of life. Forty female pre-menopausal patients between the ages of 20-40 years with mastalgia and 40 totally healthy volunteers with the same characteristics were investigated with the Short Form 36 (SF-36), Hamilton Depression Scale, and the Hamilton Anxiety Rating Scale prospectively following breast examination and radiological examination. Statistical assessments were performed using the SPSS 11.5. Anxiety levels were observed to be higher in the patient group (p = 0.04). The depression level was higher in the patient group; however, this was not statistically significant (p = 0.08). The quality of life of the mastalgia group was determined to be lower than that of the control group, and the sub-parameters of physical function (p = 0.04), body pain (p = 0.02), general health (p = 0.03), and energy (p = 0.008) were found to be significantly low. There may be a relationship between mastalgia and depression in young women with mastalgia; however, a closer relationship between anxiety and mastalgia is observed. Mastalgia affects the quality of life of an individual negatively at a significant degree.
Keywords: Mastalgia; Quality of life; Depression; Anxiety